THE EFFECT OF RESIDENTS’ PLACE ATTACHMENT ON THEIR ATTITUDE TOWARDS DEVELOPMENT OF RELIGIOUS TOURISM: THE MODERATING EFFECT OF PERSONAL BENEFIT - Limber L. Rivas; Maribel Rodríguez; LEONOR M. PÉREZ; Dolores M. Frías-Jamilena (Enlightening Tourism: A Pathmaking Journal)
Residents’ attitude towards tourism development in religious tourism destinations is especially relevant for tourism planning. Nevertheless, there are few studies that analyse how residents’ attitude towards development of religious tourism is formed. This paper analyses the effect of residents’ place attachment on their attitudes towards development of religious tourism, considering perceived impacts of tourism as mediator and the personal benefit derived from tourism as moderating effect. On the basis of a sample of 410 residents of Montecristi, a religious tourism destination of Ecuador, and using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results show that place attachment directly influences the attitude towards development of religious tourism, but mainly through the perceived impacts of tourism. Moreover, this paper finds that the influence of the perceived impacts on the support for the development of religious tourism is higher in residents with a lower personal benefit than in residents with a higher personal benefit. These findings enable a series of recommendations to be made to the agents concerned regarding the development of religious tourism in sacred destinations.